Peer relationships and adjustment at school - Ryan, Allison M.; Ladd, Gary W., 1950- (Emerald Publishing Limited : Information Age Publishing, 2012)
This volume brings together an impressive array of respected scholars to examine the varied and complex ways in which peers influence adolescents' beliefs and behaviors in the school context. The breadth of peer influence on academic and social adjustment is evident in the wide variety of topics covered in the present volume. Throughout the chapters, scholars provide unique insights regarding the complex ways that the academic and social spheres of adolescents' lives are interconnected. Collectively, the chapters in this volume expand current knowledge and theory in peer relations research by (a) exploring different types of peer relations (e.g., close friendships, peer groups) and different peer dynamics (e.g., popularity, bullying) that emerge in the school context, (b) examining different processes that explain why and how peers influence each other in school, (c) considering developmental issues during adolescence that may be critical to understanding peers and adjustment at school and (d) providing information about how teacher practices or programs influence peer relations and school adjustment. Peer Relationships and Adjustment in School is an important volume for researchers and practitioners interested in social development, peer relationships and youth engagement and achievement in school.
Keywords: Student adjustment.; Interpersonal relations in adolescence.; Education -- Special Education -- Behavioral, Emotional & Social Disabilities.; Educational administration and organization.; Teaching of students with social, emotional or behavioural difficulties.; Relating to people with visible or hidden disabilities, impairments or conditions.; elektronické knihy; electronic books